Eco‐labeling of freight transport services: Design, evaluation, and research directions. (17th March 2022) - Kirschstein, Thomas; Heinold, Arne; Behnke, Martin; Meisel, Frank; Bierwirth, Christian
Abstract: The idea of eco‐labeling is to provide customers with an easy‐to‐understand signal regarding the ecological impact of using a product or service. With this paper, we propose an eco‐labeling system for freight transportation. We discuss design options based on a common emission reporting standard and a related communication protocol. We further explain a procedure for deriving labels for shipments of goods and provide examples illustrating and evaluating the labeling process at selected land‐based freight transport services. Results indicate that eco‐labels can grade the environmental impact of a transport service reliably, even if heterogeneous goods are moved together. Finally, we outline challenges for future research associated with eco‐labeling in freight transportation markets.